جرائم الإرهاب في القانون الدولي الجنائي - المجالي، هزاع عبدالعزيز (جامعة مؤتة - عمادة البحث العلمي, 2014)
تأتي أهمية هذا البحث من كونه يتناول موضوع جرائم الإرهاب في القانون الدولي، فجرائم الإرهاب أصبحت تشكل ظاهرة عالمية لا تكاد تخلو من تأثيرها أي من دول العالم، ونظرا لأن جرائم الإرهاب اصبحت تشكل ظاهرة عالمية لا تكاد تخلو من تأثيرها أي دولة من العالم، ونظرا لأن جرائم الإرهاب أصبحت تشكل الهاجس الأكبر لتلك الدول لما لها من مساس ليس مباشر بسلامة سيادة الدول فقط وإنما ايضا بسلامة شعوبها، فجرائم القتل التي ترتكب بكافة اشكالها تعتبر خرقا واضحا لكرامة الإنسان وآدميته وحريته وحقوقه الإنسانية، لذا فإن جهود المجتمع الدولي سواء على مستوى الدول أو المنظمات الدولية سعت منذ عقود سواء من خلال الاتفاقيات والمواثيق الدولية أو المعاهدات الدولية كانت ثنائية أو متعددات الأطراف أو كانت تعقد برعاية الأمم المتحدة أو ما بين الدول نفسها إلى تضمين القوانين الوطنية والقانون الدولي بالنصوص والمبادئ القانونية التي تجرم بشكل صريح كافة الأعمال الإرهابية التي ترتكب ضد الدول أو افرادها. وقد أسفرت تلك الجهود في اقرار العديد من الاتفاقيات الدولية فنجد اليوم ما يزيد عن ثلاثة عشر اتفاقية دولية متعددة الاطراف متعلقة بمكافحة الإرهاب الدولي بجميع أشكاله، نذكر منها على سبيل المثال: (اتفاقية باريس) ١٩٢٨م، (اتفاقية جنيف) ١٩٣٧م، (اتفاقية طوكيو) ١٩٦٣م، (اتفاقية لاهاي) ١٩٧٠م، (اتفاقية مونتريال)١٩٧١م، (اتفاقية روما) ١٩٧٣م، إضافة إلى ما نص عليه النظام الأساسي للمحكمة الجنائية الدولية من جرائم أخرى مثل: جرائم الإبادة الجماعية، والجرائم ضد الإنسانية وجرائم الحرب، وجرائم العدوان. وتعد تلك الاتفاقيات ذات أهمية خاصة وفريدة، كونها تضمنت العديد من القوانين لمكافحة الإرهاب بجميع أشكاله سواء كان ذلك في البر أو البحر أو الجو، ناهيك عن الدور الذي تلعبه قواعد العرف الدولي في زيادة مرونة تعامل الدول في مكافحة هذه الظاهرة، لذا ارتأينا أن نسلط الضوء على هذا الموضوع المهم، وسوف نقوم بتقسيم الدراسة إلى ثلاثة مباحث رئيسية على النحو التالي: المبحث الأول: الإرهاب والجريمة الدولية المبحث الثاني: ماهية القانون الدولي الجنائي الدولي. المبحث الثالث: أساليب الجرائم الإرهابية في القانون الجنائي الدولي. the importance of this research from being on the theme Hraúm terrorism in international law , crimes of terrorism has become a global phenomenon that is barely free from the influence of any of the countries in the world, and because the crimes of terrorism has become a global phenomenon that is barely free from the influence of any country of the world, because the crimes of terrorism has become a major concern for those countries because of their prejudice is not a direct safety rule only states, but also the safety of their people , crimes of murder committed in all its forms is a clear violation of human dignity and his humanity, freedom and their human rights, so the efforts of the international community, both at the level of states or international organizations sought for decades, both through international conventions or international treaties, bilateral or Mtaddt parties or were held under the auspices of the United Nations or between the states themselves to include national laws and international law texts and principles of law that criminalize explicitly all the terrorist acts committed against the State or its members. Has resulted in efforts to adopt many of the international agreements we find today more than thirteen international convention multiple parties related to combating international terrorism in all its forms, among them, for example: (Paris Convention)1928, (Geneva Convention) 1937, (Tokyo Convention ) 1963 , ( Hague Convention ), 1970, (the Montreal Convention) 1971, (Rome Convention) in 1973, in addition to what was stated by the Statute of the international Criminal Court, of other crimes, such as crimes of genocide, crimes against humanity and war crimes , and crimes of aggression . The longer those agreements are especially important and unique, being included many of the laws to combat terrorism in all its forms, whether it be on land or sea or air , not to mention the role played by the rules of international custom in increasing the flexibility of dealing States in combating this phenomenon, so we decided to highlight on this important topic, and we will divide the study into three main sections as follows: The first topic: terrorism, international crime The second topic: the nature of international law, international criminal law. The third topic: the methods of terrorist crimes in international criminal law.
Keywords: الإرهاب; القانون الدولي الجنائي; مكافحة الإرهاب; جرائم الإرهاب